The Indonesian Legal Policy on Prostitution, Could it be Legalized? - Ni Luh Gede Yogi Arthani; Made Emy Andayani Citra (UNISSULA, 2023)
Prostitution is an eternal business throughout the history of human civilization. This activity has existed since the royal era until now. In terms of finance, the business of prostitution brings a huge turnover of money. Prostitute income per day is even higher than the applicable minimum wage in each district and city. This business continues to grow even though many countries prohibit prostitution. This study aims to examine regarding the causes and dimensions of violence in prostitution and the state's legal policy on prostitution. This research is a normative legal research that examines the possibility of legalizing or prohibiting prostitution. The research was conducted using statutory approaches, legal concepts and comparative law. The analysis was carried out qualitatively. The findings of this study are prostitution is influenced by educational, economic, social, legal and political factors. This activity can involve women, men, LGBT, both adults and children. However, the greatest involvements as the sex workers are women and children. Indonesia is a country that prohibits prostitution as regulated in Article 296 and 506 of the Criminal Code, as well as several other special provisions. To overcome prostitution, the Indonesian Government issued a number of policies to disband the red-light districts. There are countries in the world that prohibit prostitution like Indonesia, some allow it with strict restrictions, and some even allow state revenue from taxes.